Association between serum cotinine and α-Klotho levels among adults: Findings from the National Health and Nutrition Examination Survey 2007–2016 - Yu Yao; Ying Long; Fa-Wang Du; Yong Zhao; Xiao-Bin Luo (Tobacco Induced Diseases, 2022)
Introduction Serum cotinine is a sensitive and specific marker of tobacco smoke exposure. α-Klotho is an anti-ageing molecule, which plays an important role in several diseases. We aimed to examine the association between smoke exposure indicated by the serum cotinine and α-Klotho levels, as previous reports regarding the level of α-Klotho in smokers have been inconsistent.